Photocatalytic treatment of C.I. Reactive Red 2 - Gonçalves, Maria S. T.; Oliveira-Campos, Ana M. F.; Pinto, Elisa M. M. S.; Amorim, Maria T. P.; Hrdina, Radim; Machalický, Oldřich (Univerzita Pardubice, 2005)
Polychromatic photo degradation of C.I. Reactive Red 2 in aqueous solutions was studies in the presence of TiO2. The influence of several factors, such as pH value, irradiation time, amount of dye and TiO2 was observed in the process. The dye degradation was monitored by visible absorption spectroscopy and Chemical Oxygen Demand (COD) determinations. It was found, that the mineralization of the dey strongly depends on pH value and the rate was higher at alkali conditions (pH 12-13). The initial quantum yields of the irradiation process were determined for pH 12.
Keywords: polychromatická fotodegradace; barviva; oxid titaničitý; katalytické procesy; fotodestrukce